Dukungan Keluarga Mempengaruhi Pengetahuan, Sikap dan Perilaku Islamic Personal Hygiene saat Menstruasi pada Remaja Putri di SMP Kota Semarang - Alinka Mutiara Putri Perdana; Sri Wahyuni; Apriliani Yulianti Wuriningsih (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Menstruation was a natural process experienced by females who have entered puberty. In Islam, maintaining cleanliness during menstruation was not only essential for physical health but also has spiritual significance. Family support, especially from parents, plays a crucial role in shaping adolescents' knowledge, attitudes, and behaviors about personal hygiene during menstruation. Based on the tests conducted, there is a significant relationship between family support and knowledge (p < 0.05), attitude (p < 0.05), and behavior (p < 0.05) concerning Islamic personal hygiene during menstruation. Respondents who received high family support tended to have better knowledge, attitudes, and hygiene practices. There is a correlation between family support and knowledge, gesture, and behaviors regarding Islamic personal hygiene during menstruation among female adolescents in junior high schools in Semarang.